Global governance and local peace: accountability and performance in international peacebuilding - and Campbell, Susanna (Cambridge University Press, 2018)
Local peacebuilding and global accountability – The country context–Burundi from 1999 to 2014 – Ingos in peacebuilding–globally unaccountable, locally adaptive – International organizations in peacebuilding–globally accountable, locally constrained – Bilateral development donors–accountable for global targets, not local change